Effect of Different Cooling Regimes on the Mechanical Properties of Cementitious Composites Subjected to High Temperatures - Jiangtao Yu; Wenfang Weng; Kequan Yu (The Scientific World Journal)
The influence of different cooling regimes (quenching in water and cooling in air) on the residual mechanical properties of engineered cementitious composite (ECC) subjected to high temperature up to 800°C was discussed in this paper. The ECC specimens are exposed to 100, 200, 400, 600, and 800°C with the unheated specimens for reference. Different cooling regimens had a significant influence on the mechanical properties of postfire ECC specimens. The microstructural characterization was examined before and after exposure to fire deterioration by using scanning electron microscopy (SEM). Results from the microtest well explained the mechanical properties variation of postfire specimens.